Organoleptic Test of Smoke Cob Fish (Euthynnus affinis) Using Efhilink Fishing Equipment and A Simple Cabinet Type of Smoking Time - Suwarsih Suwarsih; Marita Ika Joesidawati (Sangia Publishing, 2020)
The purpose of this study was to determine how long the tuna smoking process takes and how long the quality of smoked fish lasts by conducting an organoleptic test. The material of this research is the organoleptic test of smoked tuna quality with the Efhilink fish fumigant and the simple cabinet type on smoking time. The method used in this study is an experimental method that is by using corn clams as fuel for smoking cobs. The conclusion of the different treatment of the Efhilink and the simple cabinet type with the analysis results can be seen that the fumigation process that is the fastest produced by the Efhilink rack 1 type fumigator is 56 minutes. This is because the working process of the Efhilink type smoker changes the shape of the smoke produced into liquid smoke by connecting the smoke pipe with the condenser so that the temperature of the Efhilink device can be hotter than the Simple Cabinet-type fumigator, besides that the position of rack 1 is very close to the smoke source. . Whereas the longest smoking process produced by a Simple Cabinet Type 3 rack smoking device is 325 minutes or 5 hours 25 minutes this is due to the working process of the Simple Cabinet Type smoking device which emits the smoke produced through the top funnel, so that the heat produced is lower. than the Efhilink-type fumigator. In addition, the position of shelf 3 is very far from the smoke source. Meanwhile, the best organoleptic test value was produced on day 3 of the two tools. Based on the results of the study, it is suggested that the fumigation process uses the Efhilink smoke device.